BMP-SMAD signaling: From pluripotent stem cells to cardiovascular commitment. (February 2016) - Orlova, Valeria V.; Chuva de Sousa Lopes, Susana; Valdimarsdottir, Gudrun
Highlights: BMP-SMAD signalling in pluripotent stem cells (PSCs). BMP-SMAD signalling pathway during preimplantation and gastrulation. BMP-SMAD signaling in cardiovascular commitment from PSCs. Abstract: Human pluripotent stem cells (hPSCs) can form all somatic cells of the body. They thus offer opportunities for understanding (i) the basic steps of early human development, (ii) the pathophysiology in human degenerative diseases and (iii) approaches to regenerative medicine and drug development. Methods for improving their differentiation to defined mesodermal derivatives in particular will benefit their use in all of these areas but most particularly applications that require cardiac and vascular tissue. However, the molecular mechanisms that regulate mesodermal development in humans are still poorly understood. Gene ablation studies in mice have shown that the signaling pathways activated by the transforming growth factor beta (TGFβ) superfamily, including the bone morphogenetic proteins (BMP), play crucial roles in mesoderm differentiation and patterning the early embryo. Understanding their interplay and interaction with other signaling pathways, how they activate and inhibit transcription factors and epigenetic regulators during self-renewal, maintenance and exit from pluripotency and differentiation could provide vital information for a range of applications. This includes disease modeling when the hPSCs are derived from patients or drug screens for diseases of mesodermal organs. Here, we review the role of the BMP-SMAD signaling pathway in pluripotent stem cells and during mesoderm differentiation with focus on the cells that make up the cardiovascular system.